A patient specific finite element simulation of intramedullary nailing to predict the displacement of the distal locking hole. (May 2018) - Mortazavi, Javad; Farahmand, Farzam; Behzadipour, Saeed; Yeganeh, Ali; Aghighi, Mohammad
Highlights: There is a three-point contact pattern between the intramedullary nail and medullary canal, only on the proximal fragment of the fractured bone. Nail deflection during intramedullary nailing occurs mainly in sagittal plane. Patient specific modeling can predict the nail deflection with a reasonably good accuracy. Patent specific modeling can be used to provide the compensatory information for fine tuning of proximally mounted targeting systems during intramedullary nailing. Abstract: Distal locking is a challenging subtask of intramedullary nailing fracture fixation due to the nail deformation that makes the proximally mounted targeting systems ineffective. A patient specific finite element model was developed, based on the QCT data of a cadaveric femur, to predict the position of the distal hole of the nail postoperatively. The mechanical interactions of femur and nail (of two sizes) during nail insertion was simulated using ABAQUS in two steps of dynamic pushing and static equilibrium, for the intact and distally fractured bone. Experiments were also performed on the same specimen to validate the simulation results. A good agreement was found between the model predictions and the experimental observations. There was a three-point contact pattern between the nail and medullary canal, only on the proximal fragment of the fractured bone. The nail deflection was much larger in the sagittal plane and increased for the larger diameter nail, as well as for more distally fractured or intact femur. The altered position of the distal hole was predicted by the model with an acceptable error (mean: 0.95; max: 1.5 mm, in different tests) to be used as the compensatory information for fine tuning of proximally mounted targeting systems.